PENDIDIKAN KARAKTER BERBASIS KELUARGA - Jalaluddin Jalaluddin (Ta'dib: Jurnal Pendidikan Islam, 2012)
The Indonesian nation is currently experiencing a degradation of almost all lines of social and moral life. The rise of cases of domestic violence, human trafficking, juvenile delinquency, "free sex", premarital sexual intercourse, corruption and so on. To deal with these conditions, for Indonesian nation needs to develop character education for the people of Indonesia. Character education is now a widespread public consumption, but what is needed most is family-based character education. Family has most decisive position. Family is an educational environment that the earliest known where every child learns naturally from it. In the formation of the character of a child, then family must be smart in choosing allowing food for children, caring children in accordance with Islamic law, and educating children with heart and based on islamic rules.